Encapsulation of Urea-Ammonium Nitrate (UAN) Solution Fertilizer in Silica-Cellulose Matrix for Slow-Release Nitrogen and Improved Growth of Pakcoy (Brassica rapa L.) - Rizki Permatasari; Choiril Azmiyawati; Sriatun Sriatun (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Nitrogen (N) is an essential macronutrient required for plant growth; however, its absorption efficiency remains relatively low due to significant nitrogen loss to the environment. To overcome this limitation, the development of slow-release fertilizers (SRF) is crucial, enabling controlled, gradual nutrient release. This study aims to develop and evaluate a cellulose-modified mesoporous silica matrix as an encapsulation material for Urea-Ammonium Nitrate (UAN) fertilizer, a liquid formulation containing urea, ammonium, and nitrate. The material was synthesized using the sol-gel method with variations including pure silica, non-calcined silica-cellulose, silica-cellulose calcined at 550°C and 700°C, and cross-linking with glutaraldehyde. Characterization techniques included Fourier Transform Infrared Spectroscopy (FTIR) for functional group identification, Scanning Electron Microscopy combined with Energy Dispersive X-ray (SEM-EDX) for morphology and elemental composition, and Gas Sorption Analyzer (GSA) for surface area and pore size analysis. The results showed that the silica-cellulose composite calcined at 550°C (SSCGK550) had the highest fertilizer release value of 893.7 ppm. Plant growth test results show that plants treated with SSCGK550 had the highest growth, with a length of 8 cm and 8 leaves per stem by day 15, whereas plants treated with conventional fertilizer (control) showed a lower growth response, with an average height of 5 cm and only 3 leaves per stem by day 15. These findings demonstrate the success of encapsulating UAN fertilizer in a silica-cellulose matrix and highlight its potential as an efficient slow-release fertilizer to support sustainable agriculture.